CONSUMER PREFERENCES AND PERCEPTION TOWARDS READY-TO-EAT FOODS AMONG URBAN CONSUMERS IN BERHAMPUR CITY, ODISHA: CONSUMER PREFERENCES AND PERCEPTION TOWARDS READY-TO-EAT FOODS - ALITA MINZ; ISHANI SAMANTRAY; MANASEE MEHER; ASHMITA BEURA (The Journal of Research ANGRAU, 2026)
Rapid urbanization and evolving lifestyles have significantly increased the consumption of Ready-to-Eat (RTE) food products in developing cities. This cross-sectional study examines the availability, popularity, nutritional perceptions and consumer preferences regarding RTE foods in Berhampur City, Odisha. A structured questionnaire was administered to 100 respondents selected through random sampling from urban and semi-urban areas. Results revealed that 55% of consumers occasionally consume RTE foods, primarily driven by convenience (50%) and taste (45-50%). While 45% of respondents perceived RTE food availability as neutral to adequate, 35% considered these products popular in the local market. Notably, 36% of consumers preferred healthy/organic RTE options, indicating rising health consciousness. However, 46% expressed skepticism about the balanced nutritional value of RTE foods, with 37% rating nutritional quality as poor. The study identifies convenience, taste and affordability as primary purchase drivers, while health benefits and brand reputation exert minimal influence. These findings provide valuable insights for manufacturers, retailers, and policymakers to balance convenience with nutritional quality in the growing RTE food sector.